(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the translation history of the Holy Koran since ancient times up to nowadays. By centuries the Koran was translated into many languages including the Azerbaijani language. After the independence the first translation of the Koran was done by the outstanding academician Vasim Mammadaliyev and prof.Ziya Bunyadov in 1991. Since then the Koran has been published in more complicated forms and with commentaries. The author notes academician Vasim Mammadaliyev’s irreplaceable contribution in the translation of the Holy Koran into the native language, which has great importance not only for his scientific activity, but also for the whole Azerbaijani theology. Key words: Islam, translation and commentary of the Holy Koran, literal.